Revised Dyadic Adjustment Scale as a Reliable Tool for Assessment of Quality of Marital Relationship in Patients on Long-Term Hemodialysis (Iranian Journal of Kidney Diseases, 2009)
Although the revised dyadic adjustment scale (RDAS) has been widely used as an indicator of the quality of marital relationship, no report is available on the reliability of this measure in patients on hemodialysis. We examined the internal consistency of the RDAS in a group of Iranian patients undergoing maintenance hemodialysis. A translated Persian version of the RDAS was self-administered to 135 patients. The internal consistency of the RDAS was tested using the Chronbach ? coefficient which was 0.898, 0.683, 0.779, 0.827, and 0.836 for the RDAS total score and the dyadic consensus, affective expression, dyadic satisfaction, and dyadic cohesion subdomains, respectively. All of the Chronbach ? scores were higher in patients with higher income and education level. Using the RDAS to examine marital relationship quality in patients on hemodialysis, the total score and almost all subscores except for dyadic consensus had adequate internal consistency.